Methods for medical device and surgical epidemiology: applications in knee replacement and COVID-19 related tracheotomy - Prats Uribe, A (2022)
Although medical devices (MDs) and surgery have been part of medicine since its start, the methods for their study in epidemiology have not kept pace with the developments in pharmacoepidemiology. The recent increased attention from society to the potential harms of unsafe implants has led to improved legislation that call for a much closer evaluation of MDs. However, the evaluation of MDs and surgery presents unique caveats and challenges, such as the ascertainment of the indication of the surgery or how to include surgeon characteristics in the analysis, that can greatly influence outcomes.